Youth on screen representing young people in film and television - Buckingham, David 1954- (Polity Press, 2021)
Right from the origins of cinema, countless films and television dramas have offered sensational and seductive representations of young people's lives. Youth is typically associated with energy, idealism and physical beauty, but it is often represented as both troubled and troubling. These representations are almost always created by adults, implicitly reflecting an adult perspective on how young people 'come of age.'